KAJIAN PENGEMBANGAN EKOWISATA PANTAI KARTA TANJUNG GUNDUL KABUPATEN BENGKAYANG - Hamdi (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
Karta Beach, located in Karamunting village has its own charm. The purpose of the study to analyze the suitability of the area for beach recreation tourism, the carrying capacity of the area, the preparation of action plans for development, and qualitative descriptive. The analysis uses Tourism Suitability Index Analysis, Regional carrying capacity, and in-depth interviews. Conclusion: 1) Karta Beach area is suitable for beach recreation with a value of 69; 2) DDK 54 people / day; and 3) Action Plan: a) arrangement of coastal axis road; b) construction of multi-purpose buildings, parking lots, water towers, warehouses, galleries, and toilet renovations.